Considering environmental values during timber harvest : a study of forest machine operators’ practice - Dahl, Ida (SLU/Dept. of Urban and Rural Development, 2015)
The Swedish environmental objective to have sustainable forests by 2020 will not be achieved with current measures taken by the forestry sector. One problem is that the mandatory environmental considerations are not taken to a satisfactory degree in regeneration felling sites. The ones performing regeneration felling and the taking or not taking of environmental considerations are the forest machine operators. The aim of this study is to develop understanding about forest machine operators’ practice, how it hinders and facilitates the taking of environmental considerations in regeneration felling from the operators’ own descriptions of their work situation, in answering the questions: What characterizes forest machine operators practice and their task of taking environmental considerations? What type of knowledge and skills are needed in order to take considerations to the environment? How can the development of forest machine operators’ skills and possibilities of taking environmental considerations be understood? Through a theoretical reading of transcripts from seven semi-structured interviews with forest machine operators, answers to these questions are given on the assumption, based on a socio-cultural perspective on practice and practical knowledge, that knowledge, intentions, aims, norms, routines and the meaning given to objects and situations are situated and developed in social interactions. The conditions for the taking of environmental considerations during timber harvesting are also assumed to be limited to the workings and properties inherent to the capitalistic system. This study shows that the lack of considerations to environmental values in regeneration sites are not due to forest machine operators' lack of competence or that the forest machine operators have unfavorable attitudes towards environmental preservation. But during regeneration felling operators need to balance the task of taking environmental considerations with other tasks. It is operators’ practical knowledge of recognizing environmental values and their skills of operating harvesting machines in varying forest landscapes that enables and guides the taking of environmental considerations. But considerations to environmental values are limited by the frames of harvesting practices and by the reality of timber production in a global capitalistic system. This study shows that the development of forest machine operators’ knowledge and skills on how to consider environmental values, are better facilitated when operators’ actions are acknowledged, questioned and analyzed in dialogue between operators, and managers of timber harvesting and environmental consideration with respect and sensibility for the others expertise and identity.